Acupuncture against the metabolic risk factors for stroke: A systematic review of systematic reviews. Issue 35 (2nd September 2022) - Xu, Ying; Zhong, Da-yuan; Liao, Xiao-qian; Wang, Xing-ping; Ge, Jin-wen; Xu, Wei-hui
Abstract : Objective: This systematic review (SR) of SRs aims aimed to evaluate the current evidence of rehabilitation interventions in stroke patients after acupuncture treatment. Methods: Full-text SRs published in Chinese and English up to December 15, 2021 were searched in PubMed, Embase, Cochrane Library, CNKI, VIP, and Wanfang databases. The PRISMA statement and the assessment of multiple systematic reviews 2 (AMSTAR 2) scale were used to evaluate the quality of the included articles. The Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system was employed to assess the outcome indicators for evidence quality evaluation. Results: A number of 42 publications were identified in this study. According to these articles, 4 metabolic areas were identified: systolic blood pressure, weight loss, glycemic index and cholesterol. The acupuncture is beneficial to improve the systolic blood pressure of patients, and the effect of acupuncture on diastolic blood pressure is better than that of sham acupuncture. The weight loss effect of acupuncture is better than that of lifestyle and western medicine. The improvement effect of acupuncture on body mass index (BMI) is also better than that of sham acupuncture. In the study of glycemic index of stroke patients, acupuncture significantly improved glycosylated hemoglobin and insulin sensitivity index compared with western medicine. In cholesterol-related research, acupuncture can effectively improve the content of triglycerides. However, studies on HDL and LDL show that acupuncture can significantly improve HDL, but has no significant effect on LDL. Conclusion: This review summarizes the available evidence and underpins findings of the acupuncture exhibited the therapeutic role in eliminating metabolic risk factors for stroke, including systolic blood pressure, weight loss, glycemic index and cholesterol. Acupuncture could have positive effects on a specific symptom, and the effects depend not only on intervention type but also on how and when the intervention is provided. And more prioritizing high-quality research in this field in the future is conducive to guiding clinical practice.